Analisis Respon Siswa Terhadap Efektivitas Pembelajaran Matematika Kelas 10 Menggunakan Video Conference - Prazella, Thalia; Pujiastuti, Heni (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2023)
The COVID-19 pandemic changed the offline learning system to online learning. Video conferencing can help teachers and students in the teaching and learning process to replace face-to-face learning into online. The purpose of this study was to find out how the effectiveness of learning mathematics using Video Conference during online learning. The research method used is a descriptive method using a survey method by describing student responses during learning using Video Conference and the results of the analysis to make conclusions. Video conferencing is effective in helping the teaching and learning process during online learning conditions. Keyword: Response, Video Conference, Mathematics, Online Learning